A One-Pot Universal Approach to Fabricate Lubricant-Infused Slippery Surfaces on Solid Substrates - Tesler, Alexander; Prado, Lucia; Khusniyarov, Marat; Thievessen, Ingo; Mazare, Anca Valentina; Fischer, Lena; Virtanen, Sannakaisa; Goldmann, Wolfgang; Schmuki, Patrik (Advanced Functional Materials, 2021)
Wetting is a surface phenomenon that commonly occurs in nature and has an enormous influence on human life. Slippery liquid-infused porous surfaces have recently been developed to support the growing demand for anti-fouling coatings. While short-chain fluorinated compounds, commonly used to reduce the surface energy of substrates, are banned due to environmental toxicity, silane-based compounds are expensive and barely scalable. In this sense, silicone-based chemistry may match the gap as a real alternative. However, the grafting approaches demonstrated so far suffered from either slow binding kinetics or are applied under harsh conditions. Here, it is demonstrated that polydimethylsiloxanes graft to virtually any substrate when illuminated by UV light serving simultaneously as a reducing surface energy agent and infusing lubricant. This procedure is applied on metals, metal oxides, and ceramics of various surface morphologies. The proposed approach is simple, fast, scalable, environmentally friendly, and of low-cost, yet forms stable lubricant-infused slippery surfaces by a one-pot process. Due to the biocompatibility of silicone-based compounds, the process is examined on plain medically applicable substrates such as scalpel blades and glass lenses that display enhanced corrosion resistance, reduced friction through incision, and repel blood staining and bacterial adhesion without deteriorating their mechanical and optical characteristics.
CRIS-Team Scopus Importer:2021-05-14
Keywords: anti-biofouling; blood-repellent coating; corrosion resistance; lubricant-infused slippery surfaces; polydimethylsiloxane